Teleconsultation success model for knowledge exchange between medical practitioners - Ramli R.; Ali N. (International Information Institute Ltd., 2023)
In addressing the many factors contributing to the success of teleconsultation implementation, studies have focused on the aspects of users' acceptance of technology. While many research may have covered important user and organizational factors, there have been limited consideration on the attributes of teleconsultation as a KMS in the studies. Often teleconsultation is referred to as a mere IT even though it is clear that activities involved during teleconsultation have suggested that the system is indeed a KMS. It is apparent that further studies can be done to examine how user related factors such as medical practitioners' attitudes and behavior, and organizational factors such as organization commitments and directions can be integrated with constructs from KMS framework. This study will focus on the integration of constructs from organizational and user perspectives with the constructs from knowledge management in organizations into one model in the context of teleconsultation. The findings of this research will provide preliminary insights on factors that may influence medical practitioners to share knowledge, and thus, use teleconsultation. 2016 International Information Institute.